Anatomical organization of MCH connections with the pallidum and dorsal striatum in the rat - Chometton, Sandrine; Cvetkovic-Lopes, Vesna; Houdayer, Christophe; Franchi, Gabrielle; Mariot, Amandine; Poncet, Fabrice; Fellmann, Dominique; Risold, Pierre-Yves (Frontiers in Systems Neuroscience, 2014)
Neurons producing the melanin-concentrating hormone (MCH) are distributed in the posterior hypothalamus, but project massively throughout the forebrain. Many aspects regarding the anatomical organization of these projections are still obscure. The present study has two goals: first to characterize the topographical organization of neurons projecting into the cholinergic basal forebrain (globus pallidus, medial septal complex), and second to verify if MCH neurons may indirectly influence the dorsal striatum (caudoputamen) by innervating afferent sources to this structure. In the first series of experiments, the retrograde tracer fluorogold was injected into multiple sites in the pallidal and medial septal regions and the distribution of retrogradely labeled neurons were analyzed in the posterior lateral hypothalamus. In the second series of experiments, fluorogold was injected to the caudoputamen and the innervation by MCH axons of retrogradely labeled cells was analyzed. Our results revealed that the MCH system is able to interact with the basal nuclei in several different ways. First, MCH neurons provide topographic inputs to the globus pallidus, medial septal complex and substantia innominata. Second, striatal projecting neurons in the cortex, thalamus and substantia nigra presumably receive only sparse inputs from MCH neurons. Third, the subthalamic nucleus is heavily innervated by MCH projections, thus, presumably serves as one important intermediate station to mediate MCH influence on other parts of the basal nuclei.